ANALISIS PENGARUH EKSPOR-IMPOR CHINA TERHADAP LAJU PERTUMBUHAN EKSPOR DAN IMPOR INDONESIA MENJELANG ACFTA DI IMPLEMENTASIKAN - Idaryani, Sri Wahyuni (JURNAL VARIASI, 2010)
Expor and import is important key for foreign exchange of a nation. The purpose of this research is to analyze the influence of Chinaâs export and import of Indonesiaâs export and import grow rate towards ACFTA implemented, quarterly data during 2007.1 â 2009.4 are used for the analysis. By using regression analyze, the result show that increasing Chinaâs import and Chinaâs GDP will increase Indonesiaâs export grow rate. And Indonesiaâs import also influenced by Chinaâs export due to highly demand of Indonesian on import products expecially Chinaâs products. Based on the situation above, the study suggest that implementation of ACFTA since January 2010, Indonesiaâs government need support local industrialists to develop their products in order that the product able to competitive with chinaâs product in international free trade and domestic trade.Keywords: Indonesiaâs export and import, Chinaâs export import, Price of export and import, Indonesiaâs Gross Domestic Product and Chinaâs Gross Domestic Product.